Igualdad, familia y matrimonio en la Constitución ecuatoriana del 2008 (Tema Central) - Barahona Néjer, Amilcar Alexander (2015)
The family is at the core of human affection, daily life, and self-realization, although it was not traditionally conceived in this way. The vindication for human dignity, liberty, and equality have brought about deep changes regarding cultural conception of diverse societies. Respect and guarantee of the freedom of lifestyle choice back up a diverse focus of family and its social and legal rights and protections. One of these protections is marriage which, by social phenomenon, has been regulated by politic, religion, and law; being an historically discriminatory institution which is currently withheld from homosexual partners. Upon this basis, the present article demonstrates how rights are affected, as well as the constitutional challenges and opportunities which are founded in the option of guarantee and protections of equal marriage in the Ecuadorian State.